An Active CNTFET Model for RF Characterization Deduced from S Parameters Measurements - Marani, Roberto; Gelao, Gennaro; Soldano, Pasquale; Gina Perri, Anna (Current Nanoscience, 2015)
In this paper a procedure for RF characterization of Carbon NanoTube Field Effect Transistors is illustrated and applied to a back-gate CNTFET. S parameters measurements up to 12 GHz are performed and a new lumped element active two-port network is proposed and deduced from these measurements. To obtain the intrinsic RF behavior of the device, we perform a straightforward static de-embedding procedure, applicable to any other CNTFET structures. In this way it is possible to evaluate the intrinsic model to implement directly in simulation software for electronic circuits CAD.
Keywords: S parameters measurements